2021
DOI: 10.3390/molecules26226950
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Carbon Nanowall and Carbon Nanotube for Anode Material of Lithium-Ion Battery

Abstract: Carbon nanowall (CNW) and carbon nanotube (CNT) were prepared as anode materials of lithium-ion batteries. To fabricate a lithium-ion battery, copper (Cu) foil was cleaned using an ultrasonic cleaner in a solvent such as trichloroethylene (TCE) and used as a substrate. CNW and CNT were synthesized on Cu foil using plasma-enhanced chemical vapor deposition (PECVD) and water dispersion, respectively. CNW and CNT were used as anode materials for the lithium-ion battery, while lithium hexafluorophosphate (LiPF6) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…When MoS 2 :graphite = 20%:80%, the charge-transfer impedance is the smallest, and its slope in the low-frequency region is the largest, indicating that the diffusion resistance of Li + in the electrode at this time is the smallest. It can be concluded that an appropriate amount of MoS 2 combined with a graphite material with better conductivity can have a synergistic effect to reduce the charge transfer resistance of the composite material and improve the diffusion efficiency of Li + [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…When MoS 2 :graphite = 20%:80%, the charge-transfer impedance is the smallest, and its slope in the low-frequency region is the largest, indicating that the diffusion resistance of Li + in the electrode at this time is the smallest. It can be concluded that an appropriate amount of MoS 2 combined with a graphite material with better conductivity can have a synergistic effect to reduce the charge transfer resistance of the composite material and improve the diffusion efficiency of Li + [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…FCNWs can be synthesized in a onestep process using plasma-enhanced chemical vapor deposition (PECVD) [7]. The pristine material, carbon nanowall (CNW), consists of vertically aligned graphene domains and has demonstrated excellent performance in various applications, including gas sensors and field-effect transistors, due to its high electron mobility, mechanical strength, and chemical stability [8][9][10]. In a previous study, the synthesis of CNW and Ag NPs in a 3D lamellar structure showed promise as a SERS substrate.…”
Section: Introductionmentioning
confidence: 99%
“…However, the theoretical capacity of the carbon anode material is relatively low at 372 mAhg −1 , and the stability of nickel and tin oxide is not guaranteed. Therefore, among carbon-based nanomaterials, carbon, carbon nanotube (CNT), and hard carbon have been used as anode materials for lithium-ion batteries through many studies [5][6][7][8][9]. Carbon-based nanomaterials have stable durability and low resistance, so lithium-ion electrons move quickly [10][11][12].…”
Section: Introductionmentioning
confidence: 99%